Life Satisfaction and Related Factors of Denture Wearers (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study is to understand the factors affecting the satisfaction of life of female denture wearers and to practice proper denture management.Method/Statistical Analysis: The subjects of this study were the elderly welfare facility residents of Seoul, 337 were selected for final analysis. Data collection was conducted by questionnaire survey method through face - to - face interview with the researchers who were fully informed about the purpose of the study after selecting the sample as the convenience sampling method. In this study, general characteristics were calculated as frequency and percentage.Findings: The age of the patients was 75-79 years old with 210, followed by 69 patients over 80 years old and 58 patients 65-74 years old. And 74 women with family members were living together. There are 159 women with religion and 140 patients with activity limitation.The results of multiple regression analysis on the factors affecting the general characteristics of female denture wearers were as follows. Among the general characteristics, age, cohabiting family and activity limitation were significant influences. In other words, life satisfaction was high in the case of the younger age, the family with the same family, the absence of the physical activity restriction, and the explanatory power of the variables was 29.9. The results of multiple regression analysis on the factors affecting the satisfaction of life using the denture of female denture wearers are as follows. Satisfaction with chewing and Satisfaction with taste were significant.Improvements/Applications: Using the right denture has a positive effect on not only the oral function but also the satisfaction of life, so efficient management habits are necessary for a happy life.